Outcomes of intravitreal anti-VEGF therapy in eyes with both neovascular age-related macular degeneration and diabetic retinopathy. Issue 12 (7th March 2016) - Bandello, Francesco; Corvi, Federico; La Spina, Carlo; Benatti, Lucia; Querques, Lea; Capuano, Vittorio; Naysan, Jonathan; Chen, Xuejing; Sarraf, David; Parodi, Maurizio Battaglia; Souied, Eric; Freund, K Bailey; et al.
Abstract : Purpose: To investigate the outcomes of intravitreal antivascular endothelial growth factor (VEGF) therapy in eyes with both neovascular age-related macular degeneration (AMD) and diabetic retinopathy (DR). Methods: Patients from four high-volume referral centres who presented with neovascular AMD and DR, and received intravitreal anti-VEGF therapy, were included. Data retrieved from medical records and multimodal imaging were analysed. Results: Forty-one eyes of 38 patients (21 male, 17 female; mean age 78±8 years) were enrolled. Median follow-up was 28±19 (12–72) months with a mean of 9.2±7.4 intravitreal anti-VEGF injections per eye were administrated. Best-corrected visual acuity (BCVA) was 0.5±0.3 logMAR; it improved significantly at 1 year (0.3±0.3 logMAR; p=0.02) and returned to baseline values at last follow-up visit (0.6±0.4 logMAR; p=0.26). Mean central macular thickness (CMT) significantly decreased from 408±150 μm to 328±104 μm at 1 year (p=0.021) and to 335±127 μm at last follow-up visit (p=0.032). The baseline severity of DR was graded as mild non-proliferative DR (NPDR) in 21 (51%) eyes, moderate NPDR in 14 (34%), severe NPDR in 4 (10%) and inactive proliferative DR in 2 (5%). At last follow-up visit, one eye graded as moderate NPDR improved to mild, one eye graded as severe NPDR improved to mild and one eye graded as severe NPDR was inactivated due to panretinal photocoagulation. Conclusions: Outcomes analysis of intravitreal anti-VEGF therapy for eyes with both neovascular AMD and DR showed stabilisation of BCVA and reduction of CMT, along with stable or improved DR stage throughout follow-up.